The impact of foreign aid on maternal mortality - Emmanuel Banchani; Liam Swiss (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
In 2010, the G8 placed renewed focus on maternal health via the Muskoka Initiative by committing to spend an additional US5 billion on maternal, newborn, and child health before 2015. Following the end of the Millennium Development Goals and the advent of the Sustainable Development Goals, maternal health issues have continued to feature prominently on the global health agenda. Despite substantial investments of foreign aid over the past decade, however, there is limited evidence on the effectiveness of foreign aid in reducing maternal mortality in low- and middle-income countries. Using data from the Organisation for Economic Co-operation and Development, the World Development Indicators, and the Institute for Health Metrics and Evaluation, this study analyses the effects of aid on maternal health in a sample of 130 low- and middle-income countries from 1996 through 2015. Our results show that the effects of total foreign aid on maternal mortality are limited, but that aid allocated to the reproductive health sector and directly at maternal health is associated with significant reductions in maternal mortality. Given these targeted effects, it is important to channel more donor assistance to the promotion of reproductive health and contraceptive use among women, as it serves as a tool towards the reduction of maternal mortality.
Keywords: 330; foreign aid; maternal mortality; Muskoka Initiative; reproductive health family planning